Teori Peter-Jarvis: Memahami Dinamika Eksternalisasi Budaya Dalam Pembelajaran Kolaboratif - Abdul Fikri Yanto; Ismail Ismail; Mardiah Astuti; Reno Anugerah Pratama (Universitas Lambung Mangkurat, 2025)
Peter Jarvis' theory of adult learning offers a rich conceptual framework for understanding the dynamics of cultural externalization in collaborative learning. This study aims to analyze how learning processes involving social interaction and experience can facilitate cultural externalization as an integral part of collaborative learning. Through the use of a qualitative approach based on literature studies, this article explores the relationship between individual experiences, group interactions, and cultural constructions produced through the learning process. The results of the study indicate that collaborative learning based on the principles of Jarvis' Theory creates a dialogic space that allows individuals to integrate personal experiences with group norms and values. Cultural externalization occurs when the results of the dialogue are expressed in the form of new symbols, practices, or knowledge that can be shared. It is identified that key elements in the dynamics of cultural externalization include openness to diverse perspectives, the ability to reflect, and the continuity of interaction in the learning context